Epistemologi Tafsir Al-Qur’an Kontekstual Abdullah Saeed Dalam Arus Perubahan Sosial-Budaya Masyarakat Kontemporer - Faiz, Abd Aziz (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This article delves into the progressive movement and the epistemological foundations of Abdullah Saeed's contextual interpretation, focusing on its pivotal role in addressing the growing disparity between Islamic sciences, particularly Quranic interpretation, and the complex realities of contemporary socio-cultural dynamics. Abdullah Saeed's contextual interpretation attempts to present an interpretive method to bridge this gap. Using a philosophical Islamic sciences approach and descriptive methods through content analysis, this paper presents the epistemological construction of Abdullah Saeed's contextual interpretation. This article finds the following two things: First, Saeed's contextual method situates Qur'anic interpretation within a discourse that is open and responsive to socio-cultural change and embraces a progressive Islamic framework. Second, Saeed's contextualist interpretive epistemology presents a discursive-comprehensive style in terms of sources, tools, methods, and knowledge validation. This style proves accommodating while transcending traditional textualist and semi-textualist interpretive approaches. The significance of this epistemology lies in its affirmation that Qur'anic interpretation is not at odds with scientific and socio-cultural considerations. Rather, it actively engages with contemporary issues such as inter-religious dialogue, human dignity, human rights, gender mainstreaming, and other pertinent matters.